Influence of Heat Transfer on MHD Oscillatory Flow for Eyring-Powell Fluid through a Porous Medium with Varying Temperature and Concentration - Al –Khafajy, Dheia Gaze Salih; Hadi, Lqaa Tareq (Iraqi Journal of Science, 2020)
The aim of this research is to study the effect of heat transfer on the oscillating flow of the hydrodynamics magnetizing Eyring-Powell fluid through a porous medium under the influence of temperature and concentration for two types of engineering conditions "Poiseuille flow and Couette flow". We used the perturbation method to obtain a clear formula for fluid motion. The results obtained are illustrated by graphs.